Motivasi Sebagai Mediasi Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Medis Instalasi Rawat Inap B RSUP Sanglah Denpasar - Wayan Arya Paramarta; I Putu Purnama Astika (UNHI Press, 2020)
This study aimed to explain the effect of work training and work environment on the performance of medical staff Inpatient Installation B Sanglah General Hospital Denpasar through motivation as an intervening variable. The type of data used in this study is qualitative and quantitative data, with data sources namely primary and secondary data. The data collection method is an interview, distributing questionnaires to respondents and library research, while the data analysis technique used Smart PLS 3.2.9. The results of this study showed that work training had a positive effect but not significant on motivation, work environment had a positive effect and significant on motivation, work training had a positive effect and significant on performance, work environment had a positive effect but not significant on performance, motivation had a positive effect but not significant on performance, work training had a positive effect but not significant on performance through motivation, work environment had a positive effect but not significant on performance through motivation medical staff Inpatient Installation B Sanglah General Hospital Denpasar.